2020
DOI: 10.1126/sciadv.abb3984
|View full text |Cite
|
Sign up to set email alerts
|

A shared neural substrate for action verbs and observed actions in human posterior parietal cortex

Abstract: High-level sensory and motor cortical areas are activated when processing the meaning of language, but it is unknown whether, and how, words share a neural substrate with corresponding sensorimotor representations. We recorded from single neurons in human posterior parietal cortex (PPC) while participants viewed action verbs and corresponding action videos from multiple views. We find that PPC neurons exhibit a common neural substrate for action verbs and observed actions. Further, videos were encoded with mix… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
45
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 45 publications
(75 reference statements)
8
45
1
Order By: Relevance
“…The present finding is in close agreement with our earlier study (Orban et al, 2019) in which phAIP was activated bilaterally when subjects attended to OMAs, rather than to the gender of the actors or color of the targets. These findings, together with the single cell studies mentioned above (Aflalo et al, 2020; Lanzilotto et al, 2019), and a recent stereo‐EEG study (Platonov et al, 2020) support the view that the identity of the OMAs is processed in this region. One difference between the two fMRI studies is that activation in phAIP was observed only in the left hemisphere in the current study.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The present finding is in close agreement with our earlier study (Orban et al, 2019) in which phAIP was activated bilaterally when subjects attended to OMAs, rather than to the gender of the actors or color of the targets. These findings, together with the single cell studies mentioned above (Aflalo et al, 2020; Lanzilotto et al, 2019), and a recent stereo‐EEG study (Platonov et al, 2020) support the view that the identity of the OMAs is processed in this region. One difference between the two fMRI studies is that activation in phAIP was observed only in the left hemisphere in the current study.…”
Section: Discussionsupporting
confidence: 68%
“…These findings are further supported by the observation that featural attention affects selective hemodynamic activity in fMRI (Cukur, Nishimoto, Huth, & Gallant, 2013; Stoppel et al., 2011), as well as by many neurophysiological experiments in non‐human primates (Bisley & Goldberg, 2010; Freedman & Ibos, 2018; Treue & Martinez Trujillo, 1999). Indeed, these latter studies have indicated that featural attention modulates the gain of tuning functions, and recent single cell studies in AIP and its human counterpart have demonstrated neuronal tuning for OMAs (Aflalo et al, 2020; Lanzilotto et al, 2019). It is theoretically true that once action/ball is repeated more than once in the video, participants have sufficient information to solve the task.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently reported an analogous relation in the parallel domain of motor function ( Aflalo et al, 2020 ; Aflalo et al, 2015 ; Rutishauser et al, 2018 ; Zhang et al, 2017 ). In these studies, we found that a shared PPC neuronal population coded for overt movements as well as cognitive motor variables including imagery, observed actions, and action verbs ( Aflalo et al, 2020 ; Aflalo et al, 2015 ; Andersen and Buneo, 2002 ; Rutishauser et al, 2018 ; Zhang et al, 2017 ). This richness of representation is made possible through a partially mixed encoding in which single neurons represent multiple variables, allowing a relatively small neuronal population (recorded through a 4 × 4 mm implanted microelectrode array) to provide many movement-related signals ( Zhang et al, 2017 ; Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 73%
“…We recorded from on average 101.6 ± 7.2 neurons ( Figure 1—figure supplement 1 ) over 14 sessions in the PPC (left hemisphere) of a tetraplegic human participant (spinal injury at levels 3–4; C3/4). In previous work, we referred to the implant area as the anterior intraparietal cortex, a region functionally defined in NHPs ( Aflalo et al, 2020 , Aflalo et al, 2015 ; Rutishauser et al, 2018 ; Zhang et al, 2017 ; Zhang et al, 2020 ; Andersen et al, 2019 ; Sakellaridi et al, 2019 ). Here, we refer to the recording site as the PC-IP, acknowledging that further work is necessary to definitively characterize homologies between human and NHP anatomy.…”
Section: Resultsmentioning
confidence: 99%